ANALYSIS OF FACTORS AFFECTING THE REPAYMENT CAPACITY OF REAL-ESTATE BUSINESSES LISTED ON HOCHIMINH STOCK EXCHANGE (HOSE) - Nguyễn Văn Thép; Tạ Quang Dũng (Tạp chí Khoa học Đại học Đà Lạt)
The study aims to help real-estate businesses improve their repayment capacity. This study utilized panel data of real-estate businesses listed on Hochiminh Stock Exchange (HOSE) in the period of 2011-2015. To help these businesses improve the repayment capacity, the author analyzed the factors that affect repayment capacity. Accordingly, the random effects model (REM) is appropriate to analyze the factors that affect the repayment capacity of real-estate businesses listed on HOSE. In particular, factors such as return on assets (ROA) and asset turnover (SOA) have positive impacts on the repayment capacity, while return on equity (ROE), debt on assets ratio (DOA), and inflation (CPI) have negative impacts.